Colonic epithelial cell-specific TFEB activation: a key mechanism promoting anti-bacterial defense in response to Salmonella infection - Rao, Shanshan; Huang, Pu; Qian, Yi-Yu; Xia, Yu; Zhang, Hongfeng (Frontiers in Microbiology, 2024)
Colitis caused by infections, especially Salmonella, has long been a common disease, making it urgent to elucidate the intricate pathogenicity in colonic tissues for the development of effective anti-bacterial approaches. Of note, colonic epithelial cells, the first line against bacteria, have gained less appreciation, and the cross-talk between epithelial cells and bacteria needs further exploration.Here, we revealed that the critical anti-bacterial effector, TFEB, was predominantly located in colonic epithelial cells rather than macrophages. Salmonella-derived LPS significantly promoted the expression and nuclear translocation of TFEB in colonic epithelial cells by inactivating the mTOR signaling pathway in vitro, and this enhanced nuclear translocation of TFEB was also confirmed in a Salmonella-infected mouse model. Further investigation uncovered that the infection-activated TFEB contributed to the augmentation of the anti-bacterial peptides expression, without affecting the intact structure of colonic epithelium and inflammatory cytokine expression.Our findings identify the preferential distribution of TFEB in colonic epithelial cells, where TFEB can be activated by infection to enhance anti-bacterial peptide expression, holding promising implications for the advancement of antibacterial therapeutics.